2004
DOI: 10.1097/01.mjt.0000101828.94820.c6
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia in Veterans Administration Nursing Home Patients

Abstract: The objective of this study was to identify differences between nursing home (NH) and nonnursing home (non-NH) patients with bacteremia regarding host risk factors, exposures, microbiology, and outcome. Between October 1995 and February 1998, 134 episodes of true bacteremia were identified at the North Chicago Veterans Administration Medical Center (NCVAMC). Seventy-eight episodes of bacteremia occurred in NH patients who stayed for at least 3 months in the NH at the NCVAMC and developed bacteremia there or 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
2
0
0
Order By: Relevance
“…Furthermore, the most common nursing-home-associated gram-positive bacterium isolated in our study was MRCNS, which corresponds with results proposed by Khayr et al 11 . In addition, the proportion of nursinghome-associated BSIs caused by MRSA, P. aeruginosa, and A. baumannii were also similar to previous reports.…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, the most common nursing-home-associated gram-positive bacterium isolated in our study was MRCNS, which corresponds with results proposed by Khayr et al 11 . In addition, the proportion of nursinghome-associated BSIs caused by MRSA, P. aeruginosa, and A. baumannii were also similar to previous reports.…”
Section: Resultssupporting
confidence: 92%
“…The literature review identified 1 study 7 of NHABSI published in 2004 that covered the period 1995-1998 and was not included in the 2005 review 1 because that review included studies published between 1980 and 2003. The findings of this study 7 were consistent with studies in the 2005 review 1 and will not be discussed further. The literature review identified 6 studies published since 2005 that met the inclusion criteria [8][9][10][11][12][13] : 2 studies evaluated exclusively NHABSI 8,9 and 4 studies compared NHABSI to community-or hospital-associated BSI.…”
Section: Resultssupporting
confidence: 90%